2010
DOI: 10.1002/cjoc.201090263
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Assembly of Vesicles by a 2,6‐Di(7‐benzamidy)quinolin‐2‐ yl)pyridine Derivative Tuned by an Amphiphilic Amide Chain

Abstract: This paper describes 2-(2-(dioctylamino)-2-oxoethyl-amino)-2-oxoethoxyl (DOAOE)-tuned self-assembly of vesicles from a 2,6-di(7-benzamidy)-quinolin-2-yl)pyridine derivative. Scanning electron (SEM), transmission electron (TEM) and optical microscopy and dynamic light scattering (DLS) studies reveal that the molecule self-assembles into vesicular structures in methanol. The influence of the transition metal ions and trifluoroacetic acid on the formation of the vesicles was investigated. The results illustrate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…The global structures exhibited discernible rings around the periphery, which should be produced through the evaporation of the entrapped solvent on the surface. [36] Figure 2B showed the AFM image of FeThpp C2DTDPA , and its height was about 33 ± 1 nm (Figure 2C), much smaller than its diameter, which may be caused by the collapse of its structure when the sample was dropped directly on the silicon wafer to dry out. [37] The EDS mapping image (Figure 2G) demonstrated that C, N, S, and Fe elements were distributed uniformly over the entire assembly vesicle, and it contains 15.93% Fe compared with the S element in CAIPs (defining Fe + S = 100%).…”
Section: Characterization Of Caipsmentioning
confidence: 99%
“…The global structures exhibited discernible rings around the periphery, which should be produced through the evaporation of the entrapped solvent on the surface. [36] Figure 2B showed the AFM image of FeThpp C2DTDPA , and its height was about 33 ± 1 nm (Figure 2C), much smaller than its diameter, which may be caused by the collapse of its structure when the sample was dropped directly on the silicon wafer to dry out. [37] The EDS mapping image (Figure 2G) demonstrated that C, N, S, and Fe elements were distributed uniformly over the entire assembly vesicle, and it contains 15.93% Fe compared with the S element in CAIPs (defining Fe + S = 100%).…”
Section: Characterization Of Caipsmentioning
confidence: 99%